Looking into “Awéwé” and “Lalaki” in the Sundanese Magazine Manglé Local Wisdom and a Corpus Analysis of the Linguistic Construction of Gender - Yuliawati et al., Susi (International Journal of Advanced Science and Technology, 2019)
This study uses methods in corpus linguistics to examine the construction of gender, based on word usage patterns of awéwé ‘woman’ and lalaki ‘man’ in a 2.9 million-word corpus of Sundanese magazine Manglé. The linguistic construction of gender is discussed as empirical evidence of how Sundanese local wisdoms may give an impact on ways of speaking about man and woman. Using the corpus software WordSmith Tools, frequency analysis demonstrates that woman was more popular to talk about than man that is indicated by the higher frequency of awéwé than of lalaki. Following this, an analysis of the top 30 significant collocates of awéwé and lalaki discovers that the following semantic categories were referenced: kin, people, relationship, body and physical appeareance and age. Other semantic categories, however, were specific to particular gender terms, i.e. general ethics found only in collocates of awéwé, while personal traits and power solely found in lalaki. A close examination of the concordances reveals that the usages of awéwé seem to represent that woman is weak and dependent on man, while the usages of lalaki tend to signify that man is strong and powerful. The result of corpus analyses is apparently in line with the Sundanese traditional knowledge that expects woman to be submissive to man. Thus, the present paper argues that corpus-based analysis can be used to investigate the manifestation of local wisdoms in language use.